IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH TERHADAP PENINGKATAN MUTU PENDIDIKAN DI MADRASAH - Hasan, Moh. Nur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
This paper tries to give a description of the importance of the implementation of the Madrasah education and autonomy. madrasah education that offers better quality with a religious culture to build the character of students who are able to apply the values and norms of religion. Several factors support the implementation of the School-Based Management in madrassas are: (1)Support of various elements present in the school, teachers, staff, parents and the head of the student, (2)adequate facilities and infrastructure, and (3)Ethos work and high spirits of all the elements are there, so that the policy issued by the school can be carried out in accordance with the goals and objectives. Factors inhibiting the implementation of the School-Based Management in madrassas are: (1)The policy of the government that are sometimes not in line with the program planned by the madrasah, (2)Most of the teachers slow in implementing planned programs, (3)Lack of response to the program as part of teacher has been planned, and (4)Teachers sometimes often do not permit entry of teaching, it inhibits the programs that have been planned school.